Bumper crops, producer incentives and persistent poverty: implications for food aid programs in Bangladesh - Dorosh, Paul A.; Shahabuddin, Quazi; Aziz, M. Abdul (International Food Policy Research Institute, 2002)
Food aid has played a useful role in Government of Bangladesh efforts to increase food security in the last three decades, adding to foodgrain availability, supplying wheat for targeted distribution to poor households, and helping to finance development projects and programs. However, sustained increases in domestic production of both rice and wheat have increased the likelihood of disincentive effects arising from continued large inflows of food aid. The analysis shows that if good rice harvests continue so that real rice prices remain at their levels of 2000, and if international wheat prices return to their average 1995-99 levels, then public wheat distribution may need to be cut to levels below the current amount of food aid received (650 thousand tons in 2000/2001) to avoid reducing domestic prices below import parity. However, resources will continue to be required for programs that increase access to food by the poor, contribute to increased utilization of food and result in improved nutritional outcomes, even if the need for food aid to increase availability of foodgrains diminishes.